2016
DOI: 10.1063/1.4961147
|View full text |Cite
|
Sign up to set email alerts
|

Hydration effects on the electronic properties of eumelanin building blocks

Abstract: Theoretical results for the electronic properties of eumelanin building blocks in the gas phase and water are presented. The building blocks presently investigated include the monomeric species DHI (5,6-dihydroxyindole) or hydroquinone (HQ), DHICA (5,6-dihydroxyindole-2-carboxylic acid), indolequinone (IQ), quinone methide (MQ), two covalently bonded dimers [HM ≡ HQ + MQ and IM ≡ IQ + MQ], and two tetramers [HMIM ≡ HQ + IM, IMIM ≡ IM + IM]. The electronic properties in water were determined by carrying out seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 62 publications
2
16
1
Order By: Relevance
“…Very recently, several computational studies pointed out the importance of taking such extrinsic contribution into account 15 16 17 18 . It was suggested that excitonic coupling effects from the interplay of geometric order and disorder of aggregate structures broaden and enhance the visible absorption spectrum of eumelanin 15 .…”
mentioning
confidence: 99%
“…Very recently, several computational studies pointed out the importance of taking such extrinsic contribution into account 15 16 17 18 . It was suggested that excitonic coupling effects from the interplay of geometric order and disorder of aggregate structures broaden and enhance the visible absorption spectrum of eumelanin 15 .…”
mentioning
confidence: 99%
“…Following our previous work [32], we have considered for this study monomeric structures composed of fundamental building blocks including DHI (5,6-dihydroxyindole) or hydroquinone (HQ) and the redox and tautomeric species, indolequinone (IQ) and quinone methide (MQ). Two dimers defined by covalent bonding of HQ and MQ (named HM) and of IQ and MQ (named IM).…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…In protic solvents, however, the structural and electronic properties of eumelanin pigments can be particularly affected by electrostatic interactions, and the role played by hydrogen bonding and long-range polarization effects in the spectroscopic properties of monomeric and oligomeric building blocks certainly deserve special attention. Indeed, we have shown that for some eumelanin building blocks in liquid water, the light absorption at higher energies is enhanced as a result of the long-range electrostatic interactions with the water environment [32]. It is also shown that the broadening of electronic absorption spectrum with a nearly monotonic decay from the ultraviolet to the near infrared can be obtained by the superposition of the electronic spectra of different monomeric and oligomeric building blocks, in line with the predictions of the chemical disorder model proposed to explain the eumelanin absorption spectrum [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Early descriptions included that of a semiconductor, distinct states and scattering, 7 and more recently excitonic coupling 10 and long-range water-induced coulombic interaction. 11 Melanin's intrinsic fluorescence has so far been similarly unrevealing as it is weak and complicated by overlapping bands, 12 thus offering little structural insight although the presence of copper ions can simplify the usual complex intrinsic fluorescence, producing only one fluorescence decay component, suggesting a single excited state and a more uniform structure. 13,14 Although the constituents of melanin are known melanin's poor solubility and unsuitability for crystallography have defied conventional approaches to finding how they are organized, with conflicting models continuously emerging.…”
Section: --------------------------------*mentioning
confidence: 99%